2019
DOI: 10.3390/mi10080530
|View full text |Cite
|
Sign up to set email alerts
|

Direct Patterning of a Carbon Nanotube Thin Layer on a Stretchable Substrate

Abstract: Solution-based direct patterning on an elastomer substrate with meniscus-dragging deposition (MDD) enables fabrication of very thin carbon nanotube (CNT) layers in the nanometer scale (80–330 nm). To fabricate the CNT pattern with CNT solution, contact angle, electrical variation, mechanical stress, and surface cracks of elastomer substrate were analyzed to identify the optimal conditions of O2 treatment (treatment for 30 s with RF power of 50 W in O2 atmosphere of 50 sccm) and mixture ratio between Ecoflex an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Although this is not a photo-sensitive polymer, the inclusion of photo-initiators and additives in the formulation of PDMS has been reported to allow photo-patterning (Iojoiu et al, 2000;Bhagat et al, 2007;Cotton et al, 2011) enabling its use in the development of NCPRs. Different groups reported the preparation of PDMS-based nanocomposites containing Au NPs (Fedoruk et al, 2013;SadAbadi et al, 2013;Romanenko et al, 2020), Ag NPs (Cong and Pan, 2009), Ag nanowires (Martinez et al, 2015;Shuai et al, 2017), magnetic NFs (Chung et al, 2011) and carbon nanotubes (Khosla and Gray, 2010;Liu and Choi, 2012;Li et al, 2019a;Lee et al, 2019). PDMS nanocomposites with carbon based nanofillers was recently reviewed (Kausar, 2020).…”
Section: The Host Matrixmentioning
confidence: 99%
“…Although this is not a photo-sensitive polymer, the inclusion of photo-initiators and additives in the formulation of PDMS has been reported to allow photo-patterning (Iojoiu et al, 2000;Bhagat et al, 2007;Cotton et al, 2011) enabling its use in the development of NCPRs. Different groups reported the preparation of PDMS-based nanocomposites containing Au NPs (Fedoruk et al, 2013;SadAbadi et al, 2013;Romanenko et al, 2020), Ag NPs (Cong and Pan, 2009), Ag nanowires (Martinez et al, 2015;Shuai et al, 2017), magnetic NFs (Chung et al, 2011) and carbon nanotubes (Khosla and Gray, 2010;Liu and Choi, 2012;Li et al, 2019a;Lee et al, 2019). PDMS nanocomposites with carbon based nanofillers was recently reviewed (Kausar, 2020).…”
Section: The Host Matrixmentioning
confidence: 99%
“…Flexible devices: Lee et al [10] demonstrated direct patterning of a carbon nanotube thin layer on a stretchable substrate.…”
mentioning
confidence: 99%